Migration and Differentiation of Neural Stem Cells Diverted From the Subventricular Zone by an Injectable Self-Assembling β-Peptide Hydrogel - Motamed, Sepideh; Del Borgo, Mark P.; Zhou, Kun; Kulkarni, Ketav; Crack, Peter J.; Merson, Tobias D.; Aguilar, Marie-Isabel; Finkelstein, David I.; Forsythe, John S. (Frontiers in Bioengineering and Biotechnology, 2019)
Neural stem cells, which are confined in localised niches are unable to repair large brain lesions because of an inability to migrate long distances and engraft. To overcome these problems, previous research has demonstrated the use of biomaterial implants to redirect increased numbers of endogenous neural stem cell populations. However, the fate of the diverted neural stem cells and their progeny remains unknown. Here we show that neural stem cells originating from the subventricular zone can migrate to the cortex with the aid of a long-lasting injectable hydrogel within a mouse brain. Specifically, large numbers of neuroblasts were diverted to the cortex through a self-assembling β-peptide hydrogel that acted as a tract from the subventricular zone to the cortex of transgenic mice (NestinCreERT2:R26eYFP) in which neuroblasts and their progeny are permanently fluorescently labelled. Moreover, neuroblasts differentiated into neurons and astrocytes 35 days post implantation, and the neuroblast-derived neurons were Syn1 positive suggesting integration into existing neural circuitry. In addition, astrocytes co-localised with neuroblasts along the hydrogel tract, suggesting that they assisted migration and simulated pathways similar to the native rostral migratory stream. Lower level of astrocytes was found at the boundary of hydrogels with encapsulated brain-derived neurotrophic factor, comparing with hydrogel implants alone.